A pilot-scale experimental study on CO2 capture using Zeolitic imidazolate framework-8 slurry under normal pressure. (15th August 2019) - Yan, Shuren; Zhu, Ding; Zhang, Zhiyong; Li, Hai; Chen, Guangjin; Liu, Bei
Highlights: Capturing of CO2 was realized using ZIF-8 slurry in a pilot-scale bubble column. CO2 concentration in the emission gas could be reduced to 0.5–2.5 mol%. The recycling loading of CO2 in the slurry reached as high as 1.53 mol/L·bar. The slurry could be regenerated under very moderate conditions. The performance of the slurry remains stable over more than 100 h of cycling. Abstract: Efficient capture of CO2 is of great significance for the reduction of greenhouse gas emissions and the control of global warming. We herein report a pilot experiment demonstrating successful carbon capture under normal pressure using flowable slurry formed with Zeolitic imidazolate framework-8 and 2-methylimidazole-glycol-water solution in continuously cycled setup composed of a sorption bubble column (with height 3.7 m and inner diameter 60 mm) and a desorption tank. A series of factors that affect the carbon capture efficiency were investigated systematically. The experimental results show that the use of finer aperture and installing baffles, lower superficial gas velocity, lower sorption temperature, higher regeneration temperature, and low regeneration pressure are favorable for carbon capture. CO2 concentration in the emission gas could be reduced from 24.9 mol% to 0.5–2.5 mol%, indicating that more than 92% of CO2 could be removed. The working loading of CO2 in the recycled slurry reached 1.53 mol/(L·bar). The slurry could be regenerated under very moderate conditions (333 K and 0.05 MPa), which are far from boiling conditions for the solvent. It was also shown that the performance of the slurry remained stable over more than 100 h of cycling. This work demonstrates that the approach based on the use of the slurry is readily applicable, and could lead to energy savings compared to the traditional amine absorption approach.